Familial nonsyndromic hearing loss with incomplete partition type II caused by novel DSPP gene mutations. (3rd August 2018) - Li, Wan-Xin; Peng, Hong; Yang, Le; Hao, Qing-Qing; Sun, Wei; Ji, Fei; Guo, Wei-Wei; Yang, Shi-Ming
Abstract: Background: Familial nonsyndromic hearing loss (NSHL) with incomplete partition type II (IP-II) is a very rare condition. Aims/Objectives: To determine the audiological feature, inheritance patterns and genetic etiology of familial NSHL with IP-II in a Chinese family with eight family members. Material and methods: Clinical data were collected from all eight family members, selected deafness genes were sequenced in proband and whole genome sequencing of seven family members was performed. Results: The proband were a pair of male nonidentical twins (III:1, III:2). Three patients in this family, including the twins and their father (II:1), were diagnosed with bilateral NSHL with IP-II, and no mutation was found in the genes of SLC26A4, GJB2, GJB3, mitochondrial 12S rRNA, and MITF. Whole genome sequencing data indicated de novo mutations of the gene DSPP, c.3085A > G and c.3087C > T, which resulted in p.N1029D and co-segregated with deafness phenotype, were the underlying genetic etiology. Conclusion and significance: Familial NSHL with IP-II is extremely rare. In this family, de novo DSPP gene mutations, were considered to be the most probable genetic etiology. And this is the first report to reveal DSPP gene mutations leading to familial NSHL with IP-II.